2021
DOI: 10.1002/cam4.4313
|View full text |Cite
|
Sign up to set email alerts
|

Ixazomib‐based maintenance therapy after bortezomib‐based induction in patients with multiple myeloma not undergoing transplantation: A real‐world study

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
(49 reference statements)
0
7
0
Order By: Relevance
“…Nonetheless, a recent meta-analysis indirectly compared lenalidomide vs. ixazomib maintenance treatment, showing a lack of benefit from ixazomib maintenance as compared with lenalidomide both in TE and NTE patients ( 72 ). Two ixazomib-based RW studies focused on front-line therapy ( 68 ) and maintenance therapy ( 69 ) in NTE patients are reported in Table 4 .…”
Section: Proteasome Inhibitorsmentioning
confidence: 99%
“…Nonetheless, a recent meta-analysis indirectly compared lenalidomide vs. ixazomib maintenance treatment, showing a lack of benefit from ixazomib maintenance as compared with lenalidomide both in TE and NTE patients ( 72 ). Two ixazomib-based RW studies focused on front-line therapy ( 68 ) and maintenance therapy ( 69 ) in NTE patients are reported in Table 4 .…”
Section: Proteasome Inhibitorsmentioning
confidence: 99%
“…33 Clinical test demonstrated that the adverse events' incidence of bortezomib-associated regimes were higher than those of ixazomib-related regimes in the therapy of relapsed/refractory MM, especially peripheral sensory neuropathy. 36 Our current study indicated that among 21 patients in IRd group, 28.56% of patients occurred adverse reaction including 2 of grade 1-2 leukopenia, 2 of grade 1-2 hemocytopenia, 1 of grade 1-2 diarrhea and 1 of grade 3-4 diarrhea, respectively. Whereas, among 31 patients in VRd group, 51.61% of patients suffered from adverse reaction containing 2 of leukopenia, 5 of hemocytopenia, 6 of peripheral sensory neuropathy, and 3 of limb numbness.…”
Section: Discussionmentioning
confidence: 48%
“…Nevertheless, research suggested that the drug‐related adverse reactions of IRd were mostly within the tolerable range 33 . Clinical test demonstrated that the adverse events’ incidence of bortezomib‐associated regimes were higher than those of ixazomib‐related regimes in the therapy of relapsed/refractory MM, especially peripheral sensory neuropathy 36 . Our current study indicated that among 21 patients in IRd group, 28.56% of patients occurred adverse reaction including 2 of grade 1–2 leukopenia, 2 of grade 1–2 hemocytopenia, 1 of grade 1–2 diarrhea and 1 of grade 3–4 diarrhea, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, two antichlamydial agent candidates-namely, N-(2-pyrazinecarbonyl)-D-phenylalanine-L-leucine boronic anhydride (BTZ) and (R)-1-(2-(2,5-dichlorobenzamido)acetamido)-3methylbutylboronic acid (MLN9708, IXA)-have been identified. BTZ and IXA are wellknown proteasome inhibitors and approved anticancer drugs for treating multiple myeloma and mantle cell lymphoma [13][14][15]. First, whether both compounds affect chlamydial growth was examined.…”
Section: Both Btz and Ixa But Not Delanzomib Strictly Suppress The Ch...mentioning
confidence: 99%